Qualitative evaluation of a hospital bereavement service: the perspective of grieving adults - Brown, Janie; Gardner, J. (Routledge, 2015)
Bereavement and grief are natural processes and the majority of people ?nd their way through their loss. However, a small minority may bene?t from professional assistance and a service that meets their needs. The aim of this study was to evaluate the impact of an Australian Hospital Bereavement Service on the next of kin of deceased patients. The service provides three consecutive tiers of support to palliative care patients and families including information and compassion, non-specialised bereavement support and specialist intervention referral to external agencies on an individual and selective basis. The research used a qualitative approach with semi-structured focus groups and thematic analysis. Major themes identi?ed were personal experience of grief; revisiting the hospital; and bereavement care experiences. We conclude assumptions should not be made about bereavement needs or grieving reactions of individuals. However, a suite of appropriate bereavement services, support groups and feedback opportunities are perceived as helpful by grieving adults. The research also highlighted how dif?cult it is for some family members to return to the hospital following the death of their loved one.